PEMERTAHANAN BAHASA MUNA DI KABUPATEN MUNA SULAWESI TENGGARA - Sailan, Zalili (LITERA, 2014)
This study aims to describe the maintenance of the Muna language in Muna Regency, Southeast Sulawesi. The data were collected using the ethnographic method by means of observations and unstructured interviews. The analysis was referred to micro and macrosociolinguistic theories. The findings are as follows. First, the population growth does not support the survival of the Muna language because of the increasing number of multiethnic newcomers. Second, the young generation's mobility gives more space to the use of Bahasa Indonesia. Third, the maintenance of the Muna Language is supported by elder people in villages but it is not supported by educated families, multiethnic families, elite groups, and school environments. Fourth, demographically, people aged 0 - 19 are not active enough in using the Muna language, those aged 20 - 49 do not care about the use of the Muna language, and those aged 50 or more still use the Muna language actively.